The culture of clinical teaching. - Pardo, Dona. (The University of Arizona., 1991)
The purpose of this exploratory case study was to describe the culture of clinical teaching through a symbolic interactionist framework, by identifying the rituals, faculty behaviors, and student behaviors and characteristics valued by faculty instructing in clinical settings, using content analysis, interviews and observation. Five faculty, one from each clinical specialty, were chosen using specific criteria. College of Nursing archives were content analyzed to ascertain written valued student behaviors and characteristics and faculty were interviewed to learn their stated beliefs. Faculty/student clinical interactions were observed to assess if faculty written and verbalized beliefs were enacted, and twelve students were interviewed for verification of transmission of the values. Peer debriefing, member checking and an audit trail ensured trustworthiness of the data. Faculty used eight rituals: Preparation, Tracking, Discourse, Closet, Repast, Selection, Maneuver, and Documentation, and three types of actions: Teaching, Role Modeling, and Caretaking to transmit their values. Teaching was utilized 55 percent of the time and involved questioning, instructing, guiding, correcting and observing. Role Modeling, used 22 percent, embodied promoting independence, helping, intervening, kidding and admitting fallibility. Caretaking was evidenced 23 percent of the instructor's time and included caring, praising, diffusing anger, allowing mistakes and sharing self. Over one hundred student behaviors and characteristics that faculty valued were identified and collapsed into six descriptors, listed in descending order: assertive, therapeutic, compliant, knowledgeable, disciplined, and skillful. Faculty placed emphasis on human, interactive skills versus knowledge and psychomotor skills, and responded to students with very caring behaviors. They utilized compassion as a way of effecting conformity, and their use of caring behaviors for the exercise of their power was evident.